2017
DOI: 10.21037/jss.2017.02.05
|View full text |Cite
|
Sign up to set email alerts
|

One and two level posterior lumbar interbody fusion (PLIF) using an expandable, stand-alone, interbody fusion device: a VariLift® case series

Abstract: Background: Surgical interventions such as posterior lumbar interbody fusion (PLIF) with and without posterior instrumentation are often employed in patients with degenerative spinal conditions that fail to respond to conservative medical management. The VariLift ® Interbody Fusion System was developed as a stand-alone solution to provide the benefits of an intervertebral fusion device without the requirement of supplemental pedicle screw fixation. Methods:In this retrospective case series, 25 patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The appropriately sized interbody device (VariLift-LX Wenzel Spine, Austin, USA) was then threaded into position with fluoroscopic guidance and expanded. The use of this expandable interbody has been described elsewhere and represents the only expandable interbody approved for standalone use by the US FDA [17][18][19][20][21][22]. After placement and expansion, the device was filled with morselized autograft from the harvested lamina mixed with allograft bone product or DBM if needed.…”
Section: Operative Techniquementioning
confidence: 99%
“…The appropriately sized interbody device (VariLift-LX Wenzel Spine, Austin, USA) was then threaded into position with fluoroscopic guidance and expanded. The use of this expandable interbody has been described elsewhere and represents the only expandable interbody approved for standalone use by the US FDA [17][18][19][20][21][22]. After placement and expansion, the device was filled with morselized autograft from the harvested lamina mixed with allograft bone product or DBM if needed.…”
Section: Operative Techniquementioning
confidence: 99%
“…The aforementioned benefits of a vertically expandable posterior spacer do not negatively affect fusion rate and sagittal balance [ 27 , 28 ]. A retrospective analysis by Yee et al [ 28 ] (n=89 patients) observed similar lumbar lordosis results after 1 year between static and expandable TLIF spacers (2° versus 5°, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis by Yee et al [ 28 ] (n=89 patients) observed similar lumbar lordosis results after 1 year between static and expandable TLIF spacers (2° versus 5°, respectively). Additionally, Barrett-Tuck et al [ 27 ] observed significantly improved pain scores following 12 months with solid fusion noted in 92.3% (n=12) of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the short term, patients who received a posterior expandable cage alone reported minor complications, such as posterior leg pain, infection, and wound problems. 27 However, long-term complications consisted of implant problems, especially subsidence, pseudoarthrosis, retropulsion, and cage breakage.…”
Section: Is Interbody Fusion Without Screw Fixation Safe?mentioning
confidence: 99%